Pemanfaatan Ekstrak Kompos dan Jamur Antagonis Trichoderma sp. untuk mengendalikan Powdery mildew pada Apel (Malus sylvestris Mill.) - Mutia Erti DWIASTUTI; Ahmad SUYOSO (Jurnal Pengendalian Hayati, 2008)
Powdery mildew disease caused by Podosphaera leucotricha is one of the key diseaseon apple trees. This disease wide spread on East Java and crop loss caused this disease for about 50%per year. The chemical control methods are not always economical or effective. Another promisingalternative is application of biological control. Trichoderma spp. are potencially as biological controlagent because its has strong antagonis characteristic. The purpose of this experiment was to determinethe optimal straw composted extract and effectivity of Trichoderma spp. isolates antagonis fungus tocontrol Powdery mildew on apple trees. The first phase was arranged in completely RandomizedDesign in laboratory by in vitro tested to determine the best isolates of fungus for futher tested. Thesecond phase was field experiment was used Randomized Block Design, two factors. The first factorwere composted extract with different cattle faeces stater and the second factor were Trichodermaspp. isolates and one control. The result of experiment indicated that laboratory and field experimentcould be control Powdery mildew. T3 is the best isolate for decrease this disease. Composted extractshowed that decrease effect to disease control in the laboratory, but didnot on the field. Strawcomposted extract with cattle faeces stater and combination of straw composted extract with cattlefaeces stater could be pursued Powdery mildew (13,88% disease intensity).